Chlorophyll breakdown during fruit ripening: Qualitative analysis of phyllobilins in the peel of apples (Malus domestica Borkh.) cv. 'Gala' during different shelf life stages. (December 2022) - Gorfer, Lisa Marie; Vestrucci, Luca; Grigoletto, Valentina; Lazazzara, Valentina; Zanella, Angelo; Robatscher, Peter; Scampicchio, Matteo; Oberhuber, Michael
Graphical abstract: Highlights: HR-LC-MS analysis of chlorophyll catabolites phyllobilins (PBs) in apples cv. Gala. Increasing abundance and diversity of chlorophyll catabolitesPBs during ripening. Chlorophyll catabolitesPBs are potential ripening indicators and component of human diet. Abstract: Chlorophyll (Chl) degradation is an important process of fruit ripening, mediated by the pheophorbide a oxygenase/phyllobilin (PaO/PB) pathway. Chl is catabolized to linear tetrapyrrolic phyllobilins that resemble the bile pigments. Determining the optimal harvest date is of pivotal importance for the fruit industry. Among the physiological changes at the onset of ripening and during shelf life, the breakdown of Chl appears as a promising indicator for fruit maturity. In addition, PBs are a frequently overlooked component of the human diet with antioxidant and antiproliferative activities. However, their relevance for a healthy diet and their potential as ripening indicator in fruit cannot be evaluated yet, as details on emergence and composition of PBs in fruit are yet elusive. Using apple ( Malus × domestica Borkh.) cv. 'Gala' as a model fruit, the Chl content and the emergence and identity of PBs were analyzed during a controlled shelf life period using UV/Vis spectroscopy and ultra-high pressure liquid chromatography coupled to high resolution quadrupole-time of flight-mass spectrometry (UHPLC-Q-TOF-MS). An in-house database with chromatographic and MS data from 51 PBs, revealed ten chlorophyll catabolites, including five NCCs, one YCC, and four DNCCs (including a previously unknown one). PBs were identified with increasing abundance and diversity from the onset of Chl degradation, suggesting a potential role as ripening indicators.